2010
DOI: 10.1186/1471-2164-11-s4-s25
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the NEMO/IKKβ association complex formation, a novel mechanism associated with the NF-κB activation suppression by Withania somnifera’s key metabolite withaferin A

Abstract: BackgroundNuclear Factor kappa B (NF-κB) is a transcription factor involved in the regulation of cell signaling responses and is a key regulator of cellular processes involved in the immune response, differentiation, cell proliferation, and apoptosis. The constitutive activation of NF-κB contributes to multiple cellular outcomes and pathophysiological conditions such as rheumatoid arthritis, asthma, inflammatory bowel disease, AIDS and cancer. Thus there lies a huge therapeutic potential beneath inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 39 publications
5
60
0
Order By: Relevance
“…Recently, it was hypothesized that WA could disrupt the formation of the IKK complex in silico; however, this appears to not be the case based on previous literature (26,27). Instead, we decided to test the hypothesis that WA could disrupt the NEMO-ubiquitin interaction.…”
Section: Withaferin a Selectively Induces The Gain-of-function Abilitmentioning
confidence: 98%
“…Recently, it was hypothesized that WA could disrupt the formation of the IKK complex in silico; however, this appears to not be the case based on previous literature (26,27). Instead, we decided to test the hypothesis that WA could disrupt the NEMO-ubiquitin interaction.…”
Section: Withaferin a Selectively Induces The Gain-of-function Abilitmentioning
confidence: 98%
“…19 In most cancer cell lines WA inhibits the proliferation of tumor cells through a G 2 /M phase cell cycle arrest, 20 and inhibits the activation of NF-kB via interaction with the IKKg subunit preventing IkB phosphorylation. 21,22 In pancreatic cancer cells, Yu et. al.…”
Section: Introductionmentioning
confidence: 99%
“…Intraportal transplantation of syngeneic islets in diabetic C57BL/6 mice, a model representing inflammatory response to transplanted islets, showed that the engraftment of islets is significantly improved by WA. While several reports have shown that WA inhibits the NF-κB pathway through its binding to NEMO/ IKKβ complex [14,15], no study has been undertaken on the use of WA to protect islets from inflammatory damage in islet transplants into diabetic mice. Despite significant work on islet reaction to inflammation, there has been little research into the contribution of islets to the immediate immune reaction.…”
Section: Discussionmentioning
confidence: 99%
“…There are several extracts from the leaves of W. somnifera, but a study by Kaileh et al identified the steroidal lactone, WA, as the most potent inhibitor of NF-κB based on the hyperphosphorylation of inhibitor of κB (IκB) kinase beta (IKKβ) preventing IκB degradation [14]. Grover et al suggested that WA inhibits NF-κB by preventing the formation of NF-κB essential modulator (NEMO)/IKKβ complex [15]. WA has been studied as an anti-inflammatory compound in cystic fibrosis [16] with further potential to treat chronic inflammatory diseases such as rheumatoid arthritis, asthma and inflammatory bowel disease [17,18].…”
Section: Introductionmentioning
confidence: 99%